2022
DOI: 10.1177/07356331221127300
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Automated Writing Evaluation on Writing Quality: A Meta-Analysis

Abstract: Automated writing evaluation (AWE) has been frequently used to provide feedback on student writing. Many empirical studies have examined the effectiveness of AWE on writing quality, but the results were inconclusive. Thus, the magnitude of AWE’s overall effect and factors influencing its effectiveness across studies remained unclear. This study re-examined the issue by meta-analyzing the results of 26 primary studies with a total of 2468 participants from 2010 to 2022. The results revealed that AWE had a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 65 publications
1
17
1
Order By: Relevance
“…We differentiated for secondary and tertiary level, finding similar effects of medium size for both. This is contrary to the findings by Ngo et al ( 2022 ) and Zhai and Ma ( 2022 ), who both found larger effects for post-secondary learners compared to learners at secondary level. However, both previous meta-analyses only included a very limited number of primary studies drawing on secondary-level samples ( k = 3 resp.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We differentiated for secondary and tertiary level, finding similar effects of medium size for both. This is contrary to the findings by Ngo et al ( 2022 ) and Zhai and Ma ( 2022 ), who both found larger effects for post-secondary learners compared to learners at secondary level. However, both previous meta-analyses only included a very limited number of primary studies drawing on secondary-level samples ( k = 3 resp.…”
Section: Discussioncontrasting
confidence: 99%
“…This should be kept in mind when verbally classifying the effect sizes. In the following, we interpret our findings in light of previous research, especially the two recent meta-analyses by Ngo et al ( 2022 ) and Zhai and Ma ( 2022 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Based on recent meta-analyses ( Fleckenstein et al, 2023 ; Graham et al, 2015 ; Li, 2022 ; Zhai & Ma, 2022b ), one promising technology-based intervention is AWE. AWE is software that uses natural language processing to provide immediate, computer-generated evaluative scores and feedback ( Hockly, 2019 ; Strobl et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…AWE capabilities have expanded in recent years ( Deeva et al, 2021 ; Huang et al, 2023 ), accompanied by increased AWE adoption in schools. Along with research evaluating the effectiveness of AWE, which shows generally positive findings ( Ersanli & Yesilel, 2023 ; Fleckenstein et al, 2023 ; Li, 2022 ; Zhai & Ma, 2022b ), it also is important that research evaluate stakeholders' perceptions of the social validity of AWE (see Shi & Aryadoust, 2022 ). Social validity refers to how the goals, procedures, and effects of an intervention are perceived by its recipients and/or implementers ( Kazdin, 1977 ; Wolf, 1978 ) and may also include perceptions of an intervention's usability, usefulness, and desirability.…”
Section: Introductionmentioning
confidence: 99%